2012
DOI: 10.2478/v10019-012-0044-9
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of electrochemotherapy by intramuscular IL-12 gene electrotransfer in murine sarcoma and carcinoma with different immunogenicity

Abstract: Background.Electrochemotherapy provides good local tumor control but requires adjuvant treatment for increased local response and action on distant metastasis. In relation to this, intramuscular interleukin-12 (IL-12) gene electro-transfer, which provides systemic shedding of IL-12, was combined with local electrochemotherapy with cisplatin. Furthermore, the dependence on tumor immunogenicity and immunocompetence of the host on combined treatment response was evaluated.Materials and methods.Sensitivity of SA-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…Although it was recently demonstrated that electrochemotherapy induces immunological cell death, the therapy on its own is not able to induce a systemic immunity, thus not having the abscopal effect . Therefore, to add a systemic component to local electrochemotherapy treatment, it was combined on a preclinical level with several immunological approaches, such as the addition of IL‐2 secreting cells, recombinant TNF‐α and also IL‐12 gene electrotransfer, which proved to be very effective . Even on its own, IL‐12 electrogene therapy was successful in the eradication of melanoma and sarcoma tumours in mice .…”
Section: Discussionmentioning
confidence: 99%
“…Although it was recently demonstrated that electrochemotherapy induces immunological cell death, the therapy on its own is not able to induce a systemic immunity, thus not having the abscopal effect . Therefore, to add a systemic component to local electrochemotherapy treatment, it was combined on a preclinical level with several immunological approaches, such as the addition of IL‐2 secreting cells, recombinant TNF‐α and also IL‐12 gene electrotransfer, which proved to be very effective . Even on its own, IL‐12 electrogene therapy was successful in the eradication of melanoma and sarcoma tumours in mice .…”
Section: Discussionmentioning
confidence: 99%
“…All the mice cured by multiple mIL-12 gene electrotransfer alone or combined with radiation were also resistant to secondary challenge, however the same phenomena was observed with mice treated with treatments used as pertinent controls (multiple therapies with electric pulse application or plasmid coding for dsRed combined with tumor irradiation) that resulted in tumors cures, due to their immunogenicity. This indicates that multiple mIL-12 gene electrotransfer alone or combined with irradiation and also treatments used as pertinent controls might have either increased the immunogenicity of SA-1 sarcoma [28,41] (increased tumor antigen availability after radiation induced apoptosis) or stimulated the immune cells (control plasmid coding for immunogenic protein) [34,42,43] leading to a better tumor immunosurveillance and prevention of tumor outgrowth after secondary challenge. Thus, in contrast to the effects of IL-12 on tumor cures its contribution to the long term immunity could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…During preclinical studies, several mechanisms that contribute to the overall effectiveness of ECT have been demonstrated. Besides the basic mechanism of increased membrane permeability leading to increased drug cytotoxicity (50), reduced tumor blood flow (vascular lock) is observed (51) and results in a vascular disruption effect of ECT (52)(53)(54)(55); an enhanced immune response is also observed (56)(57)(58). Thus, combining ECT with an immunostimulatory approach using recombinant cytokines or GET-delivered plasmids encoding these cytokines (e.g., IL-2, IL-12, IL-15, GM-CSF, and TNF-α) can give rise to a significant potentiation of ECT treatment (59)(60)(61)(62).…”
Section: Electrochemotherapymentioning
confidence: 97%